Metformin induced acute pancreatitis precipitated by renal failure. Issue 942 (13th April 2004) - Mallick, S
Abstract : Metformin is a biguanide commonly used in type 2 diabetes and considered to be a safe drug with minimal side effects. Approximately 2% of cases of acute pancreatitis may be caused by drugs, but it is not a known complication of metformin therapy. To date only one case of pancreatitis has been reported in association with metformin, but that was secondary to metformin poisoning (overdose). This is the first reported case of pancreatitis caused by a therapeutic dose of metformin (although in this case renal failure precipitated the metformin toxicity). Severe lactic acidosis is a rare but life threatening complication of metformin, which occurs particularly in patients with renal failure.